Genome-Wide Association Study on Candidate Genes Associated with Soybean Stem Pubescence and Hilum Colors - Miaomiao Zhou; Junyan Wang; Huatao Chen; Qianru Jia; Shengyan Hu; Yawen Xiong; Hongmei Zhang; Wei Zhang; Qiong Wang; Chengfu Su (Agronomy, 2024)
The colorations of stem pubescence and hilum are crucial criteria for discerning diverse soybean germplasms, governed by multiple genes that substantially influence the seed’s outward appearance quality and the resistance to abiotic stresses. This comprehensive study delved into the stem pubescence and hilum color traits across a natural population of 264 accessions during 2021 and 2022. The phenotypes of these two traits within our population were analyzed for the investigation of population genetics and evaluation of germplasm resources in the future. Numerous noteworthy SNPs associated with both traits were detected through a genome-wide association study (GWAS), with the most significant signals for 2021 and 2022 localized on chromosome 6. Seven candidate genes regulating stem pubescence color and four genes influencing hilum color were identified by analyzing the expression patterns, cold stress responses, and regulatory pathways of genes within the LD decay distance of SNPs. This study not only underscores the applicability of GWAS in unraveling the genetic basis of quality traits, but also contributes novel genetic reservoirs and research paradigms to the explorations of the soybean plant and seed color. These results provide foundational insights into the breeding improvement of seeds’ outward appearance quality and a comprehensive evaluation of soybean germplasm.